NCOG-04. PRETREATMENT VOLUME OF MR-DETERMINED WHITE MATTER INJURY (WMI) PREDICTS NEUROCOGNITIVE DECLINE AFTER HIPPOCAMPAL AVOIDANT (HA) WBRT+MEMANTINE FOR BRAIN METASTASES: SECONDARY ANALYSIS OF NRG ONCOLOGYCC001. (9th November 2020) - Bovi, Joseph; Pugh, Stephanie; Brown, Paul; Gondi, Vinai; Wefel, Jeffrey S; Tome, Wolfgang A; Gilbert, Mark; Robinson, Cliff; Benzinger, Tammie L S; Sabsevitz, David; Lee, Karen; Paulson, Eric; et al.
Abstract: PURPOSE: Previous secondary analysis of NRG/RTOG 0933 provided hypothesis-generating data supporting a relationship between larger volumes of MR-determined pre-treatment WMI and developing neurocognitive decline following HA-WBRT. The current study examines the relationship between pre-treatment WMI and neurocognitive function (NCF) following WBRT+memantine +/-HA in a substantially larger cohort. METHODS: NCF testing was performed at baseline, 2, 4, 6, and 12 months post-WBRT, and included Hopkins Verbal Learning Test–Revised (HVLT-R), Trail Making Test (TMT) Parts A and B, and Controlled Oral Word Association (COWA). Pre-treatment WMI was measured by FLAIR volume corrected for whole brain volume and corrected for the FLAIR volume associated with metastases (FLAIR/(whole brain volume – metastasis FLAIR volume). Pearson correlation coefficients were used to assess association between pre-treatment WMI and change from baseline for each standardized NCF score. RESULTS: Of 518 randomized patients, 442 (217, WBRT+Memantine; 225, HA-WBRT+Memantine) had WMI data and were included. In the entire cohort, mean FLAIR volume was 9.3cc (0.1-68.2cc), mean metastases FLAIR volume was 61.5cc (0-423.5cc), mean Whole Brain volume was 1336.4cc (949.4-2397.8cc). At 2 months, there were no significant correlations between neurocognitive test change scores and pre-treatment WMI volume. However, at 4 months, both HVLT-R Total Recall and TMT Part B change score and pre-treatment WMI volume were significantly negatively correlated on the HA-WBRT+Memantine arm (ρ=-0.22 p=0.042 and ρ=-0.27, p=0.013). At 12 months, both TMT Part A and TMT Part B change scores and pre-treatment WMI volume were significantly negatively correlated on the HA-WBRT+Memantine arm (ρ=-0.30, p=0.046 and ρ=-0.53, p< 0.001). CONCLUSIONS: Pre-treatment WMI volume was a significant imaging-biomarker predictor of post-treatment neurocognitive decline at 4-and 12-months following HA-WBRT+Memantine. This suggests patients with greater pre-treatment WMI were more susceptible to neurocognitive decline, specifically when undergoing HA-WBRT, but not following standard WBRT. Dose heterogeneity inherent to HA-WBRT delivery may contribute to these findings and are hypothesis generating.